2001
DOI: 10.1074/jbc.m011680200
|View full text |Cite
|
Sign up to set email alerts
|

Factor IXa:Factor VIIIa Interaction

Abstract: The physiologic activator of factor X consists of a complex of factor IXa, factor VIIIa, Ca 2؉ and a suitable phospholipid surface. In one study, helix 330 (162 in chymotrypsin) of the protease domain of factor IXa was implicated in binding to factor VIIIa. In another study, residues 558 -565 of the A2 subunit of factor VIIIa were implicated in binding to factor IXa. We now provide data, which indicate that the helix 330 of factor IXa interacts with the 558 -565 region of the A2 subunit. Thus, the ability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(23 citation statements)
references
References 46 publications
0
20
0
3
Order By: Relevance
“…The A2 domain is a focal point for conformational change leading to altered function as this domain contacts the protease domain of factor IXa (30). For example, differences in fluorescence anisotropy of a fluorophor-labeled factor IXa active site were observed using an isolated A2 subunit in the presence and absence of the A1 subunit compared with factor VIII heavy chain (contiguous A1-A2 domains) (31).…”
Section: Discussionmentioning
confidence: 99%
“…The A2 domain is a focal point for conformational change leading to altered function as this domain contacts the protease domain of factor IXa (30). For example, differences in fluorescence anisotropy of a fluorophor-labeled factor IXa active site were observed using an isolated A2 subunit in the presence and absence of the A1 subunit compared with factor VIII heavy chain (contiguous A1-A2 domains) (31).…”
Section: Discussionmentioning
confidence: 99%
“…Based upon experimental data supporting a direct interaction of the 558-loop of A2 with the 330-helix of factor IXa, Bajaj et al (19) proposed a model for this interface between the protease domain and the A2 subunit following docking of these structures. In the model, Asp-560 is suggested to electrostatically interact with Arg-338 (Arg-170 using the chymotrypsin number system) of factor IXa.…”
Section: A2 Variantmentioning
confidence: 99%
“…One region in A2, the 558-loop was identified as a factor IXa-interactive site by both peptide inhibition studies (17) and by the capacity of factor IXa to selectively protect factor VIIIa from activated protein C-catalyzed cleavage at Arg-562 (18). More recently, Bajaj et al (19) suggested that residues within the A2 558-loop bind to the 330-helix in factor IXa and modeled this interaction. According to this model, electrostatic, hydrophobic interactions and hydrogen bonds contribute to forming this interface.…”
mentioning
confidence: 99%
“…Positioning of the Fab took into account only the overall shape complementarity between FIXa and the Fab structure; a full docking protocol could not be performed, since the amino acid sequence of mAb AW is not known. An approximate model for the FIXa-Fab complex was then positioned next to the FVIIIa model using information previously reported for FVIIIa, and further optimization of the system was performed interactively (13,32). Modeling and structural analysis were performed on Silicon Graphics O 2 and FUEL workstations (Mountain View, CA) with the Accelrys package (available on the World Wide Web at www.accelrys.com; Accelrys, San Diego, CA).…”
Section: Effect Of Mab Aw On the Activation Of Fix By Fxia And Fviia⅐tf-mentioning
confidence: 99%